Find (g circle f)(-4)

f(x) = -x squared + 4

g(x) = 2x

### 1 Answer | Add Yours

You need to evaluate the composition of the function f(x) and g(x), such that:

(fog)(x) = f(g(x))

You need to substitute `g(x)` for x in equation of function `f(x)` , such that:

`f(g(x)) = -(g(x))^2 +4`

Substituting `2x` for `g(x)` yields:

`f(g(x)) = -(2x)^2 + 4 => f(g(x)) = -4x^2 + 4`

You need to evaluate `f(g(x))` at `x = -4` , such that:

`f(g(-4)) = -4(-4)^2 + 4 => f(g(-4)) = -64 + 4 = -60`

**Hence, evaluating `f(g(-4))` , under the given conditions, yields `f(g(-4)) = -60` .**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes